Forensic Investigation of Sudden Death in Public Places: Implications for Public Health Policy - Muhamad Khoiri (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Sudden death in public places poses a critical public health challenge with broad societal and policy implications. This review examined the role of forensic investigations in understanding sudden death and their relevance to public health policy. A systematic review was conducted following PRISMA 2020 guidelines, searching PubMed, Scopus, ScienceDirect, Google Scholar, and SINTA for studies published between 2014 and 2024. Of 96 identified articles, 15 met the inclusion criteria. Cardiovascular disease—particularly coronary atherosclerosis, myocardial infarction, and arrhythmias—was the leading cause, mostly in middle-aged men. While conventional autopsy remains the gold standard, molecular autopsy has expanded the ability to detect genetic factors in unexplained deaths. Forensic findings contribute to health strategies such as cardiovascular screening, genetic counseling, and improved emergency response systems. Strengthening forensic capacity and integrating medicolegal data into health surveillance are essential for reducing the burden of sudden death and advancing evidence-based policy.